Seasonal variations in sap flow and soil evaporation in an olive (Olea europaea L.) grove under two irrigation regimes in an arid region of Argentina - Rousseaux, Maria Cecilia (2009)
The emergence of intensively managed olive plantations in arid, northwestern Argentina requires the efficient use of irrigation water. We evaluated whole tree daily transpiration and soil evaporation throughout the year to better understand the relative importance of these water use components and to calculate actual crop coefficient (Kc) values. Plots in a 7-year-old 'Manzanilla fina' olive grove with 23% canopy cover were either moderately (MI) or highly irrigated (HI) using the FAO method where potential evapotranspiration over grass is multiplied by a given Kc and a coefficient of reduction (Kr). The Kc values employed for the MI and HI treatments were 0.5 and 1.1, respectively, and the Kr was 0.46. Transpiration was estimated by measuring main trunk sap flow using the heat balance method for three trees per treatment. Soil evaporation was measured using six microlysimeters in one plot per treatment. Both parameters were evaluated for 7-10 consecutive days in the fall, winter, mid-spring, summer, and early fall of 2006-2007. Maximum soil evaporation was observed in the summer when maximum demand was combined with maximum surface wetted by the drips and evaporation from the inter-row occurred due to rainfall. Similarly, maximum daily transpiration was observed in mid-spring and summer. Transpiration of MI trees was 30% lower than in HI trees during the summer period. However, this difference in transpiration disappeared when values were adjusted for total leaf area per tree because leaf area was 28% less in the MI trees. Transpiration represented about 70-80% of total crop evapotranspiration (ETc) except when soil evaporation increased due to rainfall events or over-irrigation occurred. We found that daily transpiration per unit leaf area had a positive linear relationship with daily potential evapotranspiration (r2 = 0.84) when considering both treatments together. But, a strong relationship was also observed between transpiration per unit leaf area and mean air temperature (r2 = 0.93). Thus, it is possible to predict optimum irrigation requirements for olive groves if tree leaf area and temperature are known. Calculated crop coefficients during the growing season based on the transpiration and soil evaporation values were about 0.65-0.70 and 0.85-0.90 for the MI and HI treatments, respectively.